Strategies for Implementing Progressive Law for Societal Development and Economic Growth - Nainggolan, Bernard (UNISSULA, 2023)
The concept of progressive law is placed in a sociological perspective where law is directed to serve the interests of society. This research aims to create a more just, sustainable and participatory economy for Indonesian society, by placing sustainability as the main focus. This research identifies the challenges faced by Third World countries, especially in the context of globalization which leads to the domination of global economic actors over resources and markets. This has led to social stratification that is increasingly felt globally, increasing inequality and presenting sustainability and justice issues. Furthermore, concrete steps are needed to improve the legal system and mechanisms that support progressive economic development, including optimizing the Anti-Monopoly Law to prevent economic concentration, as well as implementing a progressive tax system to create a fairer distribution of wealth. In addition, this research encourages the active role of local governments, community-based market mechanisms, and community agricultural development.